ANALYSES OF THE CAUSE AND EFFECT DIAGRAMMS OF EXPANDED POLYSTYRENE MANUFACTURING PROCESS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The manufacturing of expanded polystyrene is a multi-stage process. In each stage the number of technologic parameters is very high, they are intercorrelated and influence the quality of the end product. The improper combination of parameter quantitative values causes defects – deterioration of mechanical and heat insulation properties, product deformation and cracking. The planning of experiments for parameter discrimination and afterwards optimization is not practicable due to the high number of variables. That is why we used the cause and effect diagrams for the identification of the most essential parameters. After analyzing the regulation of the technological process a cause and effect diagram (the so-called”fish-bone”) was created for each stage. Further on, after having analyzed the literature data and using the experience gained in the real manufacturing process, the set of eventually most essential parameters was defined. Also the number of these parameters is quite high, however it already gives a possibility to perform purposeful experiments and make an analysis of the experimental results.